Alterações genéticas associadas ao gene apoe em pessoas com declínio cognitivo subjetivo (DCS): uma revisão sistemática - Fernandes, Carla Nunes Fonseca (Universidade Federal de São Carlos, 2022)
Subjective cognitive decline (SCD) consists of a self-perception of cognitive decline, with no objective impairment on cognitive tests and no functional impairment in activities of daily living. It represents a transitional stage between the asymptomatic state and the impairment of cognitive functions. Studies indicate that neurobiological bases participate in the process of the loss of cognitive function in the early stages of SCD. There is evidence that the neurobiological processes are related to polymorphisms in different nucleotide positions of the gene that codes for apolipoprotein E (APOE), changing the sequence of the original amino acids and modifying its structural properties. It is therefore believed that these alterations may influence the functional properties of APOE and promote the accumulation of β-amyloid plaques and the formation of neurofibrillary tangles. The molecular and physiological mechanisms leading to these clinical conditions are not yet known in detail, and therefore correlating the studies already developed aimed at further exploring these questions are critical. We performed a data collection that relates the APOE gene with DCS, through the libraries: PubMed, Mendeley and Web of Science, in the period from June to August 2021. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) model was used to construct this systematic review. Ninety studies were identified, of which only 34 met the inclusion criteria. Fifty-six studies were excluded by the following criteria: no characteristics related to DCS and APOE genotype, animal research, systematic review or meta-analysis, other genetic biomarker, protein receptor or hormonal factor, book chapter, DCS or APOE related to another disease or early onset AD, which is not associated with APOE as a risk factor, or articles that do not deal with the pre-clinical phase or year less than the stipulated date of the study. The related data pointed out in this literature review corroborate the literature in the possible existence of a clear relationship between DCS and the APOE genotype specifically in the ε4 allele in memory impairment in its early stages
Genetic alterations associated with the apoe gene in people with subjective cognitive decline (SCD): a systematic review
Keywords: APOE; DCS; Memória; Tau; β-amiloide; Alzheimer; Memory; β-amyloid; CIENCIAS DA SAUDE::ENFERMAGEM